Inhibition of PKC-θ preserves cardiac function and reduces fibrosis in streptozotocin-induced diabetic cardiomyopathy - Li, Zhao (Br J Pharmacol, 2014)
BACKGROUND AND PURPOSE: T-cell infiltration, interstitial fibrosis and cardiac dysfunction have been observed in diabetic patients with cardiovascular diseases. PKC-θ is crucial for the activation of mature T-cells. We hypothesized that inhibition of PKC-θ might protect diabetic hearts through inhibition of T-cell stimulation and maintenance of tight junction integrity. EXPERIMENTAL APPROACH: A model of type 1 diabetes was induced by streptozotocin (STZ) (50 mg kg(–1) for 5 days) in male C57BL/6J wild-type (WT) mice and Rag1 knockout (KO) mice which lack mature lymphocytes. A cell-permeable selective PKC-θ peptide inhibitor (PI) was administered i.p. (0.2 mg kg(–1)·day(–1)) for 4 weeks (first phase) and 2 weeks (second phase). At the end of the 11th week, cardiac contractile force was measured in isolated perfused hearts. Cardiac morphology and fibrosis were determined. Phosphorylation of PKC-θ at Tyr(358), infiltrated T-cells and tight junction protein ZO-1 within the hearts were detected, using immunohistochemcial techniques. KEY RESULTS: PI did not affect high blood glucose level in both WT and Rag1 KO diabetic mice. Diabetes induced cardiac fibrosis in WT mice but not in Rag1 KO mice. PI attenuated cardiac fibrosis and improved cardiac contractility of WT diabetic hearts. PI decreased expression of phosphorylated PKC-θ, reduced the infiltration of T-cells and increased ZO-1 expression within WT diabetic hearts. CONCLUSION AND IMPLICATIONS: Inhibition of PKC-θ improves cardiac function and reduces cardiac fibrosis in WT mice with streptozotocin-induced diabetes. Mature T-cells play a key role in pathophysiology of diabetic cardiomyopathy.